Artikel EVALUASI PROGRAM PELATIHAN KOMPUTER DASAR UNTUK MILENIAL DI PKBM BINA CIPTA UJUNGBERUNG.pdf - Ekawati, Widiawati (JPUS: Jurnal Pendidikan Untuk Semua, 2024)
The field circumstances surrounding the computer training program for community members in Ujungberung, particularly for Millennials to empower themselves as a support to make it easier to get employment, served as the driving force for this research. As a result, academics are eager to use evaluative research to study PKBM Bina Cipta Ujung Berung. The CIPP evaluation model (Context, Input, Process, Product) provides the foundation for the evaluative study utilized to evaluate the program as a whole. The CIPP model (Context, Input, Process, Product) was chosen by researchers because they thought it was the most appropriate model to utilize. Indicators of a training program's success include how well it meets community needs, how training activities are conducted, the results of community learning that result in new knowledge, and the development and innovation of new community skills that were previously dormant. Given this context, the overall goal of this study is to assess the design, implementation, and outcomes of the Basic Computer Training Program for Millennials. An evaluation study based on the CIPP model is employed in the procedure, which is a descriptive qualitative approach. Observations, interviews, and documentation studies are employed as instruments. The participants and administrators of beginner computer training courses for millennials are the subjects of this study. The findings demonstrated that the Evaluation of the Basic Computer Training Program for Millennials at PKBM Bina Cipta Ujungberung had been carried out well, but the shortcomings were in the implementation of the training that still used the hall, which was felt to be ineffective because there were too many activities that would reduce the participants' concentration. However, in achieving this basic computer training competency deserves to be declared successful in empowering young people.